Elastic Longitudinal Electron Scattering form Factors of 9Be - Radhi, R A; Adeeb, N M; Hashim, A K (Al-Nahrain Journal of Science, 2011)
Elastic longitudinal electron scattering form factors have been studied for 9Be (J^PI=3/2-,T=1/2)in the frame work of 1p-shell model, which considered as the core of He With five neucleons disturbuted out of the core. The basis of no-core shell model space with truncations are used also to study the effects of effective charge on the elastic longitudinal form factors. A good agreement of results are obtaining with the experimental data for both models considered in this work. The reduced transition probabilities B(C2) calculated for the two kinds of model space and for the effective charges which are used in this work.